2022
DOI: 10.2478/johh-2022-0033
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic recovery after wildfire: A framework of approaches, metrics, criteria, trajectories, and timescales

Abstract: Deviations in hydrologic processes due to wildfire can alter streamflows across the hydrograph, spanning peak flows to low flows. Fire-enhanced changes in hydrologic processes, including infiltration, interception, and evapotranspiration, and the resulting streamflow responses can affect water supplies, through effects on the quantity, quality, and timing of water availability. Post-fire shifts in hydrologic processes can also alter the timing and magnitude of floods and debris flows. The duration of hydrologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 163 publications
0
6
0
Order By: Relevance
“…Recovery processes are complexly inter‐related (Ebel et al., 2022). For example, vegetation recovery tends to influence soil hydrology in several ways, including: (a) increasing canopy development, leading to increased rainfall interception (Hoch et al., 2021) and reduced raindrop impacts (Cerdà, 1998); (b) developing roots, leading to increased macropore flow (Hubbert & Oriol, 2005); and (c) promoting increased hydrologic roughness (Liu et al., 2021), which contributes to lower runoff velocity (Rengers et al., 2016) and reduced erosion and overland flow (Cerdà & Doerr, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recovery processes are complexly inter‐related (Ebel et al., 2022). For example, vegetation recovery tends to influence soil hydrology in several ways, including: (a) increasing canopy development, leading to increased rainfall interception (Hoch et al., 2021) and reduced raindrop impacts (Cerdà, 1998); (b) developing roots, leading to increased macropore flow (Hubbert & Oriol, 2005); and (c) promoting increased hydrologic roughness (Liu et al., 2021), which contributes to lower runoff velocity (Rengers et al., 2016) and reduced erosion and overland flow (Cerdà & Doerr, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The likelihood of runoff‐generated debris flows following fire is thought to scale inversely with vegetation and soil‐hydraulic recovery of the burned area (Thomas et al., 2021). Recovery parameters return to prefire conditions over various timescales (Ebel et al., 2022; Santi & Rengers, 2022). For example, sediment yields from burned catchments can return to background rates within 3–4 years, whereas stream discharge or tree regrowth may take decades (Santi & Rengers, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This special issue presents research on the impact of fire on the Earth System. Most of the special issue (Caltabellotta et al, 2022;Ebel et al, 2022;Godoy et al, 2022;Li et al, 2022;Lucas-Borja et al, 2022;Sanin et al, 2022) is devoted to the impact of wildfire or prescribed fire on hydrological processes. The remaining articles are devoted to the heat-induced changes in soil properties (Fajković et al, 2022;Hološ et al, 2022) and the impact of biochar (produced by pyrolysis/heating biomass in the total or partial absence of oxygen) amendment on soil organic molecular markers (Atanassova et al, 2022).…”
mentioning
confidence: 99%
“…The results confirmed that wildfire can induce destruction of an SWR layer that naturally occurs at the surface of forest soils, and can create a shallow hydrophobic layer that may increase overland flow and erosion risk. Ebel et al (2022) reviewed and summarized the existing terminology and approaches for defining and assessing hydrologic recovery after wildfires. The work also critically examined the advantages and drawbacks of current recovery assessment methods, outlined challenges to determining recovery, and highlighted opportunities for advancing post-fire hydrologic recovery assessment.…”
mentioning
confidence: 99%